Laparoscopic vs Open Extravesical Ureteral Reimplantation in Pediatric Population: A Single-Center Experience: Pediatric Laparoscopic and Open Ureteral Reimplantation - Fernández-Alcaráz, David; Robles-Torres, José Iván; García-Hernández, Carlos; Guillén-Lozoya, Andrés Heriberto; Landa-Juárez, Sergio (Urology Journal, 2022)
Purpose: To evaluate the safety and efficacy of conventional laparoscopic vs open Lich-Gregoir ureteral reimplantation in pediatric vesicoureteral reflux. Material and methods: A retrospective study was conducted in a tertiary care hospital. Patients with vesicoureteral reflux who underwent open or laparoscopic Lich-Gregoir ureteral reimplantation from 2013-2020 were included. The primary outcome was resolution of reflux. Complications and perioperative characteristics were evaluated. The outcomes between open and laparoscopic surgery were analyzed. Results: A total of 110 patients and 150 ureters were included. The mean age was 4.5 years ± 3.4 and 73.6% were females. A total of 125 ureters (83.3%) underwent laparoscopic and 25 (16.6%) open Lich-Gregoir vesicoureteral reimplantation (5:1 Ratio). Resolution was reported in 112 (89.6%) for laparoscopy and 21 (84%) for open surgery (P = .42). Mean surgical time for laparoscopy and open surgery were 142.4 min ± 64.4 and 153 min ± 40, respectively (P =.29). Mean bleeding (9.5 mL ± 11.2 vs 29.6 mL ± 22.8) and length of hospital stay (2.4 days ± 2.3 vs 5.05 ± 3.1) were significantly higher with open surgery (P < .001). No significant difference in complications was reported between open surgery (32%) and laparoscopic approach (22.4%) (P = .305). Conclusion: Conventional laparoscopic vesicoureteral reimplantation with the Lich-Gregoir technique has an acceptable success rate comparable with open surgery, with shorter hospital stay, less bleeding, and less need of transfusion.